Hemodynamic changes during orotracheal intubation using Airtraq video laryngoscope and direct laryngoscope: A randomized comparative study - Upadhyaya, Sarobar; Pathak, Laxmi (Journal of Society of Anesthesiologists of Nepal, 2019)
Introduction: Direct laryngoscopy is associated with sympathetic stimulation and altered hemodynamics. A long intubation time may result in a greater in stress response. Alternative techniques using video laryngoscopes have been developed that do not require direct vocal cord visualization and may decrease the hemodynamic response. This study aimed to compare the difference between hemodynamic changes and intubation time with Airtraq video laryngoscope and conventionl Macintosh direct laryngoscope. Methods: A prospective randomized comparative study was conducted involving 100 adult patients who were undergoing elective surgeries under general anesthesia and endotracheal intubation. The patients were randomly assigned to group V (Video laryngoscope) or group D (Direct laryngoscope). In addition to the baseline vitals and vitals at various time intervals, intubation time was also recorded. We considered a difference in Heart Rate and Mean Arterial pressure of 20% to be clinically significant and statistical significance was p-value <0.05. Results: Significant difference was found in heart rates immediately after laryngoscopy (110.40 vs. 105.02 beats/minute; p<0.01) and 1 minute after intubation (109.30 vs. 106.20 beats/minute; p<0.01) with attenuation seen in video laryngoscopy group. Blood pressures were similar in both the groups at all times. Time for intubation was prolonged in video laryngoscopy group than that for direct laryngoscopy group (26.54 vs. 22.80 seconds; p<0.05). There were no adverse events associated with either of the techniques. Conclusions: The Airtraq video laryngoscopy resulted in lesser change in heart rate and longer intubation time. However, clinical impact of such a difference seemed to be insignificant.